Caregiver use of MUAC tapes in South Sudan: a three-group prospective comparison - Doocy, Shannon; Ismail, Sule; Lyles, Emily; Altare, Chiara; Bauler, Sarah; Obali, Francis; Atem, Daniel; Leidman, Eva; , The South Sudan MUAC Study Team (Frontiers in Nutrition, 2024)
Introduction Nutrition program modifications occurred globally in response to the COVID-19 pandemic. Within community management of acute malnutrition (CMAM), community screenings for acute malnutrition were replaced by caregivers monitoring child mid-upper arm circumference (MUAC), but questions remain about different MUAC tapes’ performance and acceptability for caregiver use. Methods The study was conducted in Central Equatoria and Warrap States, South Sudan, between March 2022 and January 2023. A three-group prospective non-randomized design was used to compare the performance of three MUAC tapes (UNICEF 2009, UNICEF 2020, and GOAL MAMI) used by caregivers. The primary outcome was the false negative rate (i.e., the proportion of children not identified as wasted by the caregiver but classified as wasted by enumerators). Caregivers with children aged 5–53 months were assigned to and trained on the use of 1 of the 3 tapes and followed for 8 months, including three monitoring visits and baseline/endline surveys. Results Of the 2,893 enrolled children, 2,401 (83.0%) completed baseline, endline, and two or more monitoring visits. Only 3.7% of children were identified as wasted by caregivers and 3.8% by study team measurement. Cumulative measurement agreement between caregivers and enumerators was similar by tape. False negative and false positive rates were both <0.5% overall and similar among the tapes. There were differences in training needs and durability between the tapes, but all three were acceptable and performed equally well. Discussion Caregiver measurement of child MUAC is feasible in South Sudan. The three MUAC tapes were acceptable, and caregivers could measure accurately with minimal support. All tapes performed similarly and are appropriate for use in Family MUAC programs in South Sudan. There were indications that the UNICEF 2020 tape may be less durable; the GOAL MAMI tape has the added benefit of being suitable for assessments of infants <6 months of age.